Management of persistent idiopathic facial pain (PIFP): an international Delphi study - Lindfors, Erik; Alstergren, Per; Benoliel, Rafael; Conti, Paulo; Durham, Justin; Goulet, Jean-Paul; Komiyama, Osamu; List, Thomas; May, Arne; Mitsikostas, Dimos-Dimitrios; Nixdorf, Donald R.; Pigg, Maria; et al. (Cephalalgia, 2025)
Background/Aim - Persistent idiopathic facial pain (PIFP) is a rare condition with a lifetime prevalence of approximately 0.03%. It is characterized by persistent daily facial pain without identifiable cause and presents diagnostic and therapeutic challenges due to unknown pathophysiology, symptom overlap with other painful disorders, and limited evidence-based treatments. The aim of this Delphi study was to establish international consensus-derived guidelines for the management of patients with PIFP. - Methods - A three-round Delphi study was conducted with 16 international pain experts, each with ≥10 years of clinical experience in pain management and extensive peer-reviewed publications. The first round involved open-ended questions, and the qualitative data were analyzed using systematic text condensation, resulting in a quantitative questionnaire with 42 statements. Subsequent rounds employed Likert-scale responses to these statements. Consensus was defined as ≥80% agreement or disagreement. In addition, if 11-12 (68-75 percent) out of the 16 experts agreed or disagreed, consensus was not reached, but a majority was considered to have a particular opinion. - Results - Consensus was reached in 35 out of the 42 statements (83%), emphasizing multidisciplinary collaboration and avoidance of invasive procedures in the treatment of PIFP. In an additional three statements (7%) a majority of the experts agreed with each other. In four statements (10%), no consensus or majority was reached. Pharmacological treatments, including tricyclic antidepressants, serotonin-norepinephrine reuptake inhibitors, and gabapentinoids, may be considered; however, opioids should generally be avoided in the treatment of PIFP. Patient education and behavioral therapies are important interventions, and the most important measure of therapeutic success is improved quality of life - Conclusion - The present Delphi study has established internationally derived consensus guidelines and recommendations for the evaluation and comprehensive management of patients with PIFP. This is a first step in gathering knowledge for future evidence-based guidelines and more specific treatment recommendations. These international expert consensus guidelines recommend a multi- or interdisciplinary approach in managing PIFP, avoiding invasive interventions and prioritizing patient-centered outcomes.
Erstmals veröffentlicht: 2. Dezember 2025
Gesehen am 17.02.2026